Making waves : integrating coastal conservation and development - Brown, Katrina, 1960-; Adger, W. Neil.; Tompkins, Emma L., 1966- (London ; Sterling, VA : Earthscan, 2002)
"This book is important reading for researchers and students in geography, development studies and environmental planning and also for practitioners in natural resource management and coastal zone management."--BOOK JACKET.
Ch. 1. Conservation and Development -- Ch. 2. Institutions in the Coastal Zone -- Ch. 3. Making Choices -- Ch. 4. Tools for Integration -- Ch. 5. Doing Trade-off Analysis -- Ch. 6. Building Successful Institutions -- Ch. 7. Integrating Conservation and Development.
Includes bibliographical references (p. 147-158) and index.
Keywords: Coastal zone management; Sustainable development